ANALISIS KINERJA MANAJEMEN BERDASARKAN BALANCED SCORECARD - Jumingan Jumingan (Jurnal Bisnis dan Manajemen (Journal of Business and Management), 2015)
The purpose of the research was to help CV. Angkasa manager in measuring business growth level and increasing capability and also commitment personal, They were expected could increase employee productivity and make production time more efficient so that able to increase service quality to customer.The research is case study was applied on CV. Angkasa, Using descriptive methodology. Variables in this research using forth perspective in Balanced Scorecard are financial perspective, customer perspective, internal business process perspective, learning and growth perspective .The results showed (1) financial on CV. Angkasa was good, (2) most of customer’s were satisfied on its product’s even though there were complaint of delay product’s distribution (3) inefficiency production time was reason of delay product’s distribution occurred (4) lower employee ethos was caused by lower company attention which had on impact to relationship between employee and manager that will affect employee productivity.